2016
DOI: 10.1007/s00426-016-0804-z
|View full text |Cite
|
Sign up to set email alerts
|

Do experts see it in slow motion? Altered timing of action simulation uncovers domain-specific perceptual processing in expert athletes

Abstract: Abstract:Accurate encoding of the spatio-temporal properties of others' actions is essential for the successful implementation of daily activities and, even more, for successful sportive performance, given its role in movement coordination and action anticipation.Here we investigated whether athletes are provided with special perceptual processing of spatio-temporal properties of familiar sportive actions. Basketball and volleyball players and novices were presented with short video-clips of free basketball th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…Existing studies showed significantly improved time estimation ability following short-term training for estimating specific time intervals (Healy et al, 2015). In addition, some long-trained athletes had better timing ability in their own sports items (Chen et al, 2014; Vicario et al, 2017), which also indirectly proved our viewpoint. The results of the two indicators related to time estimation in the present study also verified the present study’s hypothesis.…”
Section: Discussionsupporting
confidence: 78%
“…Existing studies showed significantly improved time estimation ability following short-term training for estimating specific time intervals (Healy et al, 2015). In addition, some long-trained athletes had better timing ability in their own sports items (Chen et al, 2014; Vicario et al, 2017), which also indirectly proved our viewpoint. The results of the two indicators related to time estimation in the present study also verified the present study’s hypothesis.…”
Section: Discussionsupporting
confidence: 78%
“…Accordingly, supporting evidence for the TEC also suggests that experience in action planning facilitates the tendency to anticipate similar actions of others toward distal effects when these actions are congruent with those previously learned (Knoblich and Flach, 2001; Wilson and Knoblich, 2005; Prinz, 2006). This suggests that experts acquired a form of anticipatory behavior that is developed as a function of action planning experience, a notion which has been frequently observed in paradigms that have reported expert-novice differences in anticipatory behavior across a variety of sporting expertise domains (Cañal-Bruland et al, 2011; Vicario et al, 2017; Murphy et al, 2018).…”
Section: Introductionmentioning
confidence: 73%
“…There is some evidence that decelerating time is a useful mechanism in situations beyond immediate threat and danger. A recent study suggests that altered time perception can be a result of extensive training, in that expert athletes are able to make better predictions based on enhanced processing of simulated actions, which internally seem to be slowed down in time [ 50 ].…”
Section: Discussionmentioning
confidence: 99%